139 Using the 'Leadership Time Capsule' to maximise learning in a crisis. (16th November 2020) - Shelton, Fenella; Boylan, Johnny; Jenkins, Paul; Conley, Harriet; Thurlow, Jane
Abstract : Background: When the COVID-19 pandemic was announced by the World Health Organisation on 11/03/2020, hospitals quickly began preparing for the potential impact on healthcare. During this crisis multi-professional teams across the NHS developed and implemented new models of service at pace. Aims: In times of crisis there can be tendency to first panic and then forget. As doctors and clinical leaders in training, utilising this as a learning experience is vital. We propose a phased learning model to reflect on this unprecedented period with the aim of strengthening our leadership skills. Method: The proposed 'leadership time capsule' is a continuous reflective process rather than a single stand-alone exercise enabling the user to learn from the pandemic as we move forward but also look back on the crisis and reflect in the moment. This learning tool is aimed for trainees and consists of five phases; Reflection, Consolidation, Growth, Embedding, and Evaluation. Integral to the time capsule are signposts to resources and toolkits. As leadership fellows, we have piloted the capsule reflecting on four different trainee perspectives: Impact on training Redeployment Telemedicine Remote working Discussion: This tool provides a template for reflective practise on our experience, realising and sharing the lessons that have been learnt. As a group of fellows, this tool was used as a 'shared experience' process exploring leadership in our various environments, learning from our experiences and realising how we can develop as leaders going forward. This reflective time capsule highlights the importance of learning from significant challenges faced during the pandemic. Conclusion: Active participation in the leadership time capsule facilitates the process of building on experiential learning during a crisis. Critical lessons from this process can inform trainee leadership development to ensure competences and confidence when facing future challenges.